Active efflux of tetracycline encoded by four genetically different tetracycline resistance determinants in Escherichia coli. - McMurry, L (1980)
Tetracycline resistance encoded by four genetically different determinants residing on plasmids in Escherichia coli was shown to be associated in each case with an energy-dependent decrease in accumulation of the antibiotic in whole cells in which resistance had been induced. The different class determinants examined were those on plasmids RP1 (class A), R222 (class B), R144 (class C), and RA1 (class D). This decrease in accumulation was attributable to an active efflux, because everted (inside-out) membrane vesicles made from tetracycline-induced E. coli cells containing any one of the four plasmids were shown to concentrate tetracycline by an active influx. This active uptake was not seen in inside-out vesicles from sensitive cells or uninduced R222-containing cells. In vesicles from induced R222-containing cells, the efflux appeared to be carrier-mediated with a Km of about 6 microM. These results demonstrate that active export of tetracycline is a common component of the mechanism for tetracycline resistance encoded by different plasmid-borne determinants in bacteria.